Experiment on liquid spreading - Haryono. (2011)
The development in the study of liquid spreading process has been remarkable because it is of utmost importance in many practical industrial applications such as ink-jet printing, surface coating, and painting. Besides, there are also many applications in biomedical engineering. In this research project, the objectives is to investigate the spreading behaviours of liquid droplets on solid substrates by varying the surface tension of liquid droplets and tuning the surface features of the solid. The influence of surface roughness and wrinkled wavelength on the spreading behaviour is experimentally studied.